Waste to Energy: Response Surface Methodology for Optimization of Biodiesel Production from Leather Fleshing Waste. (3rd February 2019) - Dagne, Henok; Karthikeyan, R.; Feleke, Sisay
Abstract : Background. The demand for diesel fuel is constantly increasing, requiring its alternate that could be sustainable, technically feasible, price competitive, and ecologically acceptable. Biodiesel is one of ecologically acceptable substitute for the conventional fuels. Methods. Sufficient lime fleshing waste was collected from Addis Ababa tannery share company. The limed fleshing waste in the wet condition was delimed using boric acid, dried, chopped, and subjected to Soxhlet extraction using petroleum ether solvent. The oil was treated by orthophosphoric acid and distilled water to remove gums. The pretreated oil was subjected to homogeneous base catalyzed transesterification. Response surface was used to optimize the process variables. GC-MS was used to see composition of the biodiesel produced. Result. The oil yield of the goat, hide, and sheep delimed fleshing wastes were 23.08%, 12.05%, and 26.7%, respectively. The conversion to biodiesel by KOH-catalyzed transesterification was achieved above 96% under optimum conditions: a methanol-to-oil molar ratio of 6:1, catalyst amount of 1 % w/w, and reaction temperature of 60°C for an hour reaction time. Conclusion. It was proven that fleshing wastes from tanneries whose storage and disposal are both troublesome and costly could be transformed to a fuel with low emission values and a performance close to diesel fuel.